PENGARUH KEDISIPLINAN TERHADAP EFEKTIVITA SPEMBELAJARAN DI SMP NEGERI 6 MEDAN - Husin Sah; S Sunardi (STIT Al-Ittihadiyah Labuhanbatu Utara, 2019)
This research uses a type of quantitative research. Data collection techniques in this study used questionnaire distribution to students, with samples of class VIII as many as 40 people. This research was conducted at Medan State Middle 6, on Jalan Bahagia No. 45, Medan City. Based on the results of this study, we can conclude that (1). Based on the calculation shows the average value = 28.75 standard deviation 8.48 and the price of variance 1.42 this indicates that the discipline of learning is quite good. (2). Based on the calculation shows the average value = 28, standard deviation 2.47 and price variance 1.57 this indicates that the effectiveness of learning is also quite good. (3). There is a significant influence between discipline on the effectiveness of learning in SMP Negeri 6 Medan with a high influence because r-count is 0.70, with t test 0.602, while based on the test of determination shows that the effect of variable X on Y variable is 49%, this shows that the influence of disciplinary variables on the effectiveness of learning is at a high level of influence.